Comprehensive stress management - Greenberg, Jerrold S. (McGraw-Hill Higher Education, 2011)
"Comprehensive Stress Management helps students identify, understand, and manage the stressors that most affect their lives. Written in an informal, anecdotal style, the text presents the latest research findings on the physical, psychological, sociological, and spiritual aspects of stress. The text also provides an in-depth discussion of a wide variety of coping skills, including relaxation techniques, behavior change interventions, and strategies for defusing physiological arousal. This engaging, easy-to-read text gives students the tools they need to cope with stress in an increasingly stressful world. Accompanying the text are instructor and student resources on the Online Learning Center"--Provided by publisher.